High platelet reactivity and clinical outcome – Fact and fiction - Sibbing, Dirk; Byrne, Robert A.; Bernlochner, Isabell; Kastrati, Adnan (Thrombosis and Haemostasis, 2011)
In patients suffering from acute coronary syndromes or undergoing percutaneous coronary intervention, oral antiplatelet treatment is routinely administered with the primary aim of inhibiting platelet-mediated thrombus formation and subsequent abrupt vessel occlusion. Simultaneous inhibition of blood platelet cyclooxygenase-1 by aspirin and of the P2Y12 receptor by clopidogrel or prasugrel is currently recommended in this setting. Inter-individual response variability to aspirin and especially to clopidogrel is the subject of much debate as evidence has grown over the years linking an attenuated response to treatment with the occurrence of ischaemic events. Consequently, the clinical entity of high (on-treatment) platelet reactivity (HPR) was born and subsequently characterised in numerous studies over the last decade. Until recently, alternative treatment options were limited in patients exhibiting HPR. At present the antiplatelet therapy landscape is changing with the advent of prasugrel and ticagrelor as alternative and more potent treatment options. Different tests for monitoring platelet function are available and are being increasingly employed in research projects and clinical routine. These tests may prove useful for achieving optimal platelet inhibition for the individual patient, and several centres now incorporate such testing in day-to-day practice. Widespread adoption of this practice and incorporation into clinical guidelines awaits the results of ongoing trials in which treatment is changed based on platelet function monitoring. This review aims to summarise available facts and fiction in relation to platelet function testing and reactivity with a particular focus on P2Y12 receptor inhibition in patients undergoing coronary stent placement.
Keywords: Platelets; antiplatelet agents; platelet function testing; thrombosis; P2Y12 receptor